Psychological therapies for the treatment of mental disorders in low- and middle-income countries affected by humanitarian crises - Purgato, Marianna; Gastaldon, Chiara; Papola, Davide; van Ommeren, Mark; Barbui, Corrado; Tol, Wietse A (Cochrane database of systematic reviews, 2018)
People living in humanitarian settings in low- and middle-income countries (LMICs) are exposed to a constellation of stressors that make them vulnerable to developing mental disorders. Mental disorders with a higher prevalence in these settings include post-traumatic stress disorder (PTSD) and major depressive, anxiety, somatoform (e.g. medically unexplained physical symptoms (MUPS)), and related disorders. A range of psychological therapies are used to manage symptoms of mental disorders in this population. To compare the effectiveness and acceptability of psychological therapies versus control conditions (wait list, treatment as usual, attention placebo, psychological placebo, or no treatment) aimed at treating people with mental disorders (PTSD and major depressive, anxiety, somatoform, and related disorders) living in LMICs affected by humanitarian crises. We searched the Cochrane Common Mental Disorders Controlled Trials Register (CCMDCTR), the Cochrane Central Register of Controlled Trials (Wiley), MEDLINE (OVID), Embase (OVID), and PsycINFO (OVID), with results incorporated from searches to 3 February 2016. We also searched the World Health Organization (WHO) trials portal (ICTRP) and ClinicalTrials.gov to identify any unpublished or ongoing studies. We checked the reference lists of relevant studies and reviews. All randomised controlled trials (RCTs) comparing psychological therapies versus control conditions (including no treatment, usual care, wait list, attention placebo, and psychological placebo) to treat adults and children with mental disorders living in LMICs affected by humanitarian crises. We used standard Cochrane procedures for collecting data and evaluating risk of bias. We calculated standardised mean differences for continuous outcomes and risk ratios for dichotomous data, using a random-effects model. We analysed data at endpoint (zero to four weeks after therapy); at medium term (one to four months after therapy); and at long term (six months or longer). GRADE (Grades of Recommendation, Assessment, Development, and Evaluation) was used to assess the quality of evidence for post-traumatic stress disorder (PTSD), depression, anxiety and withdrawal outcomes. We included 36 studies (33 RCTs) with a total of 3523 participants. Included studies were conducted in sub-Saharan Africa, the Middle East and North Africa, and Asia. Studies were implemented in response to armed conflicts; disasters triggered by natural hazards; and other types of humanitarian crises. Together, the 33 RCTs compared eight psychological treatments against a control comparator.Four studies included children and adolescents between 5 and 18 years of age. Three studies included mixed populations (two studies included participants between 12 and 25 years of age, and one study included participants between 16 and 65 years of age). Remaining studies included adult populations (18 years of age or older).Included trials compared a psychological therapy versus a control intervention (wait list in most studies; no treatment; treatment as usual). Psychological therapies were categorised mainly as cognitive-behavioural therapy (CBT) in 23 comparisons (including seven comparisons focused on narrative exposure therapy (NET), two focused on common elements treatment approach (CETA), and one focused on brief behavioural activation treatment (BA)); eye movement desensitisation and reprocessing (EMDR) in two comparisons; interpersonal psychotherapy (IPT) in three comparisons; thought field therapy (TFT) in three comparisons; and trauma or general supportive counselling in two comparisons. Although interventions were described under these categories, several psychotherapeutic elements were common to a range of therapies (i.e. psychoeducation, coping skills).In adults, psychological therapies may substantially reduce endpoint PTSD symptoms compared to control conditions (standardised mean difference (SMD) -1.07, 95% confidence interval (CI) -1.34 to -0.79; 1272 participants; 16 studies; low-quality evidence). The effect is smaller at one to four months (SMD -0.49, 95% CI -0.68 to -0.31; 1660 participants; 18 studies) and at six months (SMD -0.37, 95% CI -0.61 to -0.14; 400 participants; five studies). Psychological therapies may also substantially reduce endpoint depression symptoms compared to control conditions (SMD -0.86, 95% CI -1.06 to -0.67; 1254 participants; 14 studies; low-quality evidence). Similar to PTSD symptoms, follow-up data at one to four months showed a smaller effect on depression (SMD -0.42, 95% CI -0.63 to -0.21; 1386 participants; 16 studies). Psychological therapies may moderately reduce anxiety at endpoint (SMD -0.74, 95% CI -0.98 to -0.49; 694 participants; five studies; low-quality evidence) and at one to four months' follow-up after treatment (SMD -0.53, 95% CI -0.66 to -0.39; 969 participants; seven studies). Dropout rates are probably similar between study conditions (19.5% with control versus 19.1% with psychological therapy (RR 0.98 95% CI 0.82 to 1.16; 2930 participants; 23 studies, moderate quality evidence)).In children and adolescents, we found very low quality evidence for lower endpoint PTSD symptoms scores in psychotherapy conditions (CBT) compared to control conditions, although the confidence interval is wide (SMD -1.56, 95% CI -3.13 to 0.01; 130 participants; three studies;). No RCTs provided data on major depression or anxiety in children. The effect on withdrawal was uncertain (RR 1.87 95% CI 0.47 to 7.47; 138 participants; 3 studies, low quality evidence).We did not identify any studies that evaluated psychological treatments on (symptoms of) somatoform disorders or MUPS in LMIC humanitarian settings. There is low quality evidence that psychological therapies have large or moderate effects in reducing PTSD, depressive, and anxiety symptoms in adults living in humanitarian settings in LMICs. By one to four month and six month follow-up assessments treatment effects were smaller. Fewer trials were focused on children and adolescents and they provide very low quality evidence of a beneficial effect of psychological therapies in reducing PTSD symptoms at endpoint. Confidence in these findings is influenced by the risk of bias in the studies and by substantial levels of heterogeneity. More research evidence is needed, particularly for children and adolescents over longer periods of follow-up.